Aplicación del método Montessori en la Educación Sensorial de los niños del Subnivel Preparatoria de la Unidad Educativa Aloasí en el año lectivo 2020 - 2021. - Almache Tigse, Emilia Maribel (2021)
The present investigation addressed the problem that arises because the teachers applied a traditional methodology based mainly on worksheets, leaving aside experimentation and therefore a low level in the development of sensory skills was evidenced in the students. Faced with this, the objective has been to strengthen sensory education through the application of the Montessori method in children of the Preparatory Sub-level of the "Aloasí" Educational Unit, taking into account that this methodology encourages learning based on active exploration through of the senses. This research had a qualitative-quantitative approach, with a projective research type and with a feasible and applied project modality; The techniques used were an interview with the authorities, a survey of the teachers, and an observation sheet applied to the students. According to the applied survey, it was determined that 75% of the teachers very rarely promoted activities for direct exploration by the students, which has limited their sensory development; Thus, it was also found that 75% of teachers, very few times, have applied the Montessori methodology, which is why the proposal "I play fun and learn with the senses" was designed: Workshops for sensory education with the application of the Montessori Method, in which didactic and environmental materials were used, allowing to improve the sensory capacities in infants, and favor the teaching-learning process. In addition, the “Sensory Kids” web page was created with fun activities to provide feedback on the applied workshops, through the use of new educational technologies, generating great expectations and excitement for learning.